Application of Appropriate Technology for Automatic Hatching Machines in the Kelompok Ternak Bebek Mukti in Rajamandala Village - Sumaryana, Yusuf; Kusmayadi, Andri; Sundari, Ristina Siti; Heryadi, D Yadi; Nurcahya, Intan (Pascasarjana Universitas Mataram, 2024)
Automatic incubator is an incubator device designed to hatch eggs artificially with automatically controlled temperature, humidity, and egg turning settings, in the hope of increasing the success rate of hatching, saving time and energy, and enabling hatching on a larger scale. The purpose of this community service is to apply appropriate technology for automatic egg hatching to improve the knowledge, skills, accessibility, and income of farmers in Rajamandala Village. This program is a Kosabangsa scheme through a collaboration between Universitas Perjuangan Tasikmalaya and Universitas Siliwangi. This activity starts in September 2024 to December 2024 in Rajamandala Village, Rajapolah District, Tasikmalaya Regency. Kosabangsa activities consist of various activities, namely socialization / counseling regarding automatic incubators, training on their application which can be controlled using Android, and assistance in the application of automatic incubator technology to partners until their marketing activities. The target partner for this activity is Kelompok Ternak Bebek Mukti with a total of 20 group members as participants in the activity. The results of this community service activity show that the application of automatic incubator technology in Kelompok Ternak Bebek Mukti is able to increase the percentage of hatching power and reduce the hatching time compared to the application of manual incubator technology that is commonly used. The output of this activity is able to increase the knowledge, skills, accessibility, and income of Kelompok Ternak Bebek Mukti partners in the egg hatching process